Knowledge of warning signs, presenting symptoms and risk factors of coronary heart disease among the population of Dubai and Northern Emirates in UAE: a cross-sectional study - Khan, Nelofar Sami; Shehnaz, Syed Ilyas; Guruswami, Gomathi Kadayam; Ibrahim, Salwa Abdelzaher Mabrouk; Mustafa, Sana Abdul Jabbar (Nepal Journal of Epidemiology, 2017)
Background: To evaluate the level of knowledge regarding warning signs, presenting symptoms and risk factors associated with coronary heart disease (CHD) among population of Dubai and Northern Emirates in UAE. Materials and Methods: A cross sectional survey of 1367 residents of Dubai and Northern Emirates was conducted using a self-administered questionnaire. Results: Respondents were classified into two groups: Young Adult Population (YAP; 18-24 years of age) and General Population (GP; 25 years and older). Majority of participants were males (56.7%) and of South Asian (57.5%) or Middle-Eastern (30.8%) ethnicity. Regarding presenting symptoms of CHD, chest pain was identified by around 80% of population, whereas pain in the left shoulder was recognized by 61% of GP and 44% of YAP. Atypical symptoms were poorly identified. Regarding risk factors, only one-fourth population knew that males were at higher risk compared to premenopausal females. Few knew that the risk increases in females after menopause and that the risk is higher for females who smoke and use oral contraceptives. 62% knew that the survivors of a heart attack are at high risk of recurrences. Except for tobacco smoke, hypercholesterolemia and hypertension, knowledge of other risk factors was not satisfactory. Older adults and females had comparatively higher level of knowledge. Conclusion: Knowledge level of many of the symptoms and risk factors of CHD is unsatisfactory. There is, therefore, a need to increase the awareness in the population of UAE. The knowledge gaps identified through this study can be addressed through health campaigns to increase the awareness about warning signs, symptoms and modifiable risk factors.